PEMBERDAYAAN KELOMPOK TANI TERNAK SAPI MELALUI PENGEMBANGAN HIJAUAN DI SULAWESI UTARA - Elly, F.H.; Manese, M.A.V.; Polakitan, D. (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2014)
The cattle have the role of importance for welfare of this group in North Sulawesi. Its problems is availability feed often fall short the requirement of cattle own group. Based on these problems has made   the study of the empowerment group to develop forage for cattle feed. The rationale that food availability is a major constraint to increased production of beef. The quality and quantity of forage consumed feed cattle owned by farmers is very low. Knowledge of the group to supply a continuous feed is still very low. Extension and application of science and technology is easier to do for the group. Planting forage that has been done in an effort to meet the needs of feed by cattle as well as to optimize the utilization of idle land. Introductions superior forage has been done by empowering groups of cattle. In conclusion, the development has been done for some groups through education about the benefits of the development and practice of planting quality grass forage. Introductions grass dwarft conducted with the aim to increase the supply of feed for the cattle. Advice for the government to facilitate the development of forage in North Sulawesi.
Keywords: group, cattle, forage